In vitro synergism of combinations of colistin with selected antibiotics against colistin-resistant Acinetobacter baumannii - Percin, Duygu; Akyol, Selcan; Kalin, Gamze (GMS Hygiene and Infection Control, 2014)
[english] Aim: The in vitro activity of colistin in combination with sulbactam, netilmicin, and vancomycin against colistin-resistant strains was investigated. Furthermore, the clonal relationship of the strains was analyzed. Methods: Clonal relationship was investigated using rep-PCR. To screen for synergysm, the fractional inhibitory concentration index (FICI) was calculated using checkerboard assay. The killing kinetics of the combination of colistin with vancomycin was assessed using time-kill assay. Results: Three different clones were found among 10 clinical isolates of colistin-resistant strains. Thereof, 8 strains were susceptible to netilmicin. Synergistic interaction was detected in 1 strain with the combination of colistin-netilmicin, in 5 strains with colistin-sulbactam, and in 9 strains with colistin-vancomycin. None of combinations had antagonistic activity. Colistin-vancomycin combination resulted in rapid bactericidal activity. Conclusion: These results show a distinct in vitro synergism between colistin and vancomycin, which might be useful to treat infection with multiple-resistant strains, prevent emergence of resistant strains, and to lower doses for both antibiotics to be used.